The evolution and function of the spermatophylax in bushcrickets (Orthoptera: Tettigoniidae) - Vahed, Karim (1994)
In certain species of cricket and bushcricket (Orthoptera; Ensifera), the male transfers an elaborate spermatophore to the female at mating. This consists of a sperm-containing ampulla and an often substantial, sperm-free, gelatinous mass known as the spermatophylax. After mating, the female eats the spermatophylax before consuming the ampulla. The spermatophylax is particularly well developed in the bushcrickets (Tettigoniidae) and can contribute to a loss of as much as 40% of male body weigh at mating in some species. Recently, there has been considerable debate over the selective pressures responsible for the evolution and maintenance of the spermatophylax and other forms of nuptial feeding in insects. Two different, though not mutually exclusive, functions have been suggested for the spermatophylax: 1) nutrients from the spermatophylax may function to increase the weight and\or number of eggs laid by the female, i.e. may function as paternal investment; 2) the spermatophylax may function to prevent the female from eating the ampulla before complete ejaculate transfer, i.e. may be regarded as a form of mating effort. In this study, a comparative approach combined with laboratory manipulations were used in an attempt to elucidate the selective pressures responsible for the origin, evolutionary enlargement and maintenance (= function) of the spermatophylax in bushcrickets.